The Changing Face of Employee Silence in Different Organizational Cultures affecting Job Engagement - Shah, Syed Rehmat; Bibi, Zainab; Karim, Jahanvash; Mohammad, Nida (The journal of contemporary issues in business and government, 2021)
Organizational culture is an important factor that has a positive and negative effect on employees’ job engagement and silent behavior. Literature suggested four types of organizational cultures such as Power Culture, Role Culture, Achievement culture, and Support culture that influences the employee’s Job engagement behavior. The study aimed to explain the relationship between organizational culture and employees’ Job engagement through the mediation of employee silence in public sector universities of Quetta, Balochistan. 300 questionnaires were distributed among which 200 responses were obtained using convenience sampling method with cross-sectional design. Findings suggested that there is a significant relationship between organizational culture and job engagement. The mediating effect of employee silence was also found to be significant in the relationship between organizational culture and job engagement.